2018
DOI: 10.1021/acs.energyfuels.8b02570
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Thermodynamic Properties of Diesel Fuel and In-Cylinder Gas for Diesel Engine Combustion Investigation

Abstract: The study of the thermodynamic properties of engine fuels and the in-cylinder gas is involved in the analysis of chemical compound reaction and the thermodynamic analysis of fuel and gas, which is quite important in engine combustion investigations because the fuel chemical energy converts into internal work energy during this stage. Although the research on the thermodynamic properties of fuel and in-cylinder gas has lasted a few decades, with the development of new fuel types, developing general models with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…As a consequence, the charge density rises, increasing volumetric efficiency significantly. In addition, ethanol has a lower adiabatic flame temperature, cetane number, and ignition quality than gasoline. , Heidari et al tested biodiesel and bioethanol mixed diesel made from soybean oil. The fuel density and CN of tested fuel dropped as the biodiesel blending ratio was increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the charge density rises, increasing volumetric efficiency significantly. In addition, ethanol has a lower adiabatic flame temperature, cetane number, and ignition quality than gasoline. , Heidari et al tested biodiesel and bioethanol mixed diesel made from soybean oil. The fuel density and CN of tested fuel dropped as the biodiesel blending ratio was increased.…”
Section: Introductionmentioning
confidence: 99%
“…However, adding butanol resulted in a slight reduction in engine torque and BP and increased fuel consumption. Zhang et al 70 observed an increase in the BSFC and BTE when up to 15% butanol was added to the palm biodiesel-diesel blend (B20). Another researcher discovered that adding up to 10% butanol to a Jatropha biodiesel-diesel blend (B20) reduced the engine BSFC by 3.9% on average at constant engine load and varied speeds.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently employed method is to assume the thermodynamic parameters as constant according to empirical [23] or experimental data [24], or calculate them by the properties and mass fraction assuming that the working medium consists of several basic species [16] . It is reported in [26] that the latter method can achieve higher accuracy as it considers the variation of in-cylinder working medium composition and thermodynamic properties [26]. Ding [27] investigated the thermodynamic properties of the fuel and the in-cylinder working medium in diesel engines by using a first principles calculation method considering the thermodynamic properties functions of the working medium temperature and composition.…”
Section: Introductionmentioning
confidence: 99%